2002
DOI: 10.1023/a:1014644307518
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The present data indicate an effect of vigabatrin on the inner retinal layers. Since abnormalities of the oscillatory potentials were seen in all patients with visual field defects a dysfunction of GABA-ergic retinal cell transmission might be assumed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…There are also indications of the presence of GABA receptors on photoreceptors and horizontal cells. In the present study, OPs were decreased in both high-dose and low-dose rabbits, reflecting disturbances in inner retinal function, in accordance with several clinical studies revealing OP alterations [11,13,18,19,23,[25][26][27][28]. b-wave amplitudes derived from the isolated cone responses both in rabbits [37,38] and humans [16,49], a well-known phenomenon in VGB treatment [11, 13, 16, 18-20, 22-25, 49],which also has been described in rats [39].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…There are also indications of the presence of GABA receptors on photoreceptors and horizontal cells. In the present study, OPs were decreased in both high-dose and low-dose rabbits, reflecting disturbances in inner retinal function, in accordance with several clinical studies revealing OP alterations [11,13,18,19,23,[25][26][27][28]. b-wave amplitudes derived from the isolated cone responses both in rabbits [37,38] and humans [16,49], a well-known phenomenon in VGB treatment [11, 13, 16, 18-20, 22-25, 49],which also has been described in rats [39].…”
Section: Discussionsupporting
confidence: 92%
“…The cause of the visual field defects is still not fully understood. Numerous studies have revealed alterations of full-field ERG (ff-ERG) responses [11,13,16,[18][19][20][21][22][23][24][25][26][27][28], suggesting retinal damage as the origin of visual field defects. VGB medication has been correlated to a reduction of rod b-wave amplitudes and cone b-wave amplitudes, as well as to a decline of amplitudes of oscillatory potentials (OPs), reflecting inner retinal function.…”
Section: Introductionmentioning
confidence: 99%
“…In some patients, the abnormalities in mfERG amplitudes appeared to correspond well with VF defects [43,47], whereas in other patients the abnormalities may be more diffuse than VF findings [43] or have a poor correlation [42,45]. Besch et al [48] observed delayed multifocal oscillatory potentials in patients taking VGB with marked VF defects but without visual complaints and with normal visual acuity, color vision and dark adaptation thresholds. This finding indicates that VGB-related VF defects may be a result of inner retinal dysfunction.…”
Section: Vgb Retinopathymentioning
confidence: 99%